The Dynamics of Javanese Culture in the Nuswantara Trilogy - Damaryanti, Dewi Azizah; Sayuti, Suminto A. (Humaniora: Journal of Indonesia Culture and Society, 2025)
The shifting meaning of Javanese culture is a central theme in Tunggono's Nuswantara trilogy. This topic is important to explore, as the social criticism embedded in these fictional works warrants careful analysis. This descriptive qualitative research aims to explain the role of Javanese locality as a critique of sociocultural dynamics in the trilogy. Swingewood's sociology of literature and van Peursen's theory of cultural dynamics are applied as analytical frameworks. The researcher serves as a human instrument, gathering data through heuristic reading, hermeneutic interpretation, and note-taking. The data are processed using content analysis, which includes condensation, display, conclusion drawing, and verification. The findings indicate that the Javanese cultural dynamics in the trilogy can be categorized into three domains. First, mystical thought encompasses Hindu–Kejawen practices associated with shamans, the controversial jamasan keris ritual, offerings (sajen) and incense (dupa) to summon spirits (dedemit), mystical gamelan, and the perception of spiritual knowledge as identical with supernatural science. Second, ontological thought presents social critiques that challenge mystical traditions, contending that such beliefs do not correspond to the authentic essence of Javanese locality. Third, functional thought highlights critiques that link cultural practices to their societal and practical functions, underscoring the adaptability of Javanese culture within contemporary contexts. Tunggono’s cross-cultural engagement contributes to revitalizing discourse on Javanese cultural dynamics in literature, carried out with a strong sense of intellectual responsibility. The research affirms that Javanese culture remains open to interpretation, reflection, and critical inquiry, offering rich possibilities for ongoing scholarly examination of its evolving significance.